EFEKTIVITAS PELAKSANAAN PROGRAM GENERASI BERENCANA DALAM MENINGKATKAN KESEHATAN REPRODUKSI REMAJA DI KOTA YOGYAKARTA - Dwi Wiliantining Pyas; Lena Satlita (Yogyakarta State University, 2017)
This research aims to find out the effectiveness of the implementation of the Generasi Berencana program in Yogyakarta City along with the supporting and inhibiting factors. This research used qualitative approach with descriptive method. The results showed that the implementation of Generasi Berencana program in Yogyakarta City had not been effective, as seen from five indicators: (1) The policy had not been effective in overcoming teenagers problem, (2) Implementers had quite effective seen from the division of duties and authority, (3) The target had not been effective yet because the intervention target had not ready to support the Genre Program, (4) The policy environment had effective but the external environment had not been effective, and (5) The process had not been effective because teenagers and families with teenagers had not understood the substance of the GenRe Program. The supporting factors were the easiness of communication and counseling training. While the inhibiting factors were low public participation, moral deviation, and time limitations of each individual.Keywords: Effectiveness, GenRe Program, dan Teenagers